The Effect of Audit Knowledge, Accountability and Independence on Internal Audit Quality - Alkatiri, Ali; Basuki, Ferry Hendro; Loupatty, Linda Grace (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study evaluates the influence of audit knowledge, accountability, and independence on the quality of internal audits at the Regional Inspectorate Office of East Seram Regency, Maluku Province. Using a quantitative approach, the study involved 30 auditors as samples, with data collected through questionnaire surveys. The analysis was conducted using Multiple Linear Regression to test the influence of these variables. The results indicate that audit knowledge has a positive and significant effect on the quality of internal audits. However, the variables of accountability and independence do not show a positive and significant effect on the quality of internal audits. The study emphasizes the importance of enhancing audit knowledge to improve internal audit quality, while the aspects of accountability and independence do not demonstrate a significant relationship in the context of this research.